Assessing the Contribution and Effectiveness of Motor Vehicle Taxes in Enhancing Regional Revenue: Evidence from Central Java Province - Subroto, Vivi Kumalasari; Sudibyo, Sukemi Kamto (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
Local governments in Indonesia rely significantly on local tax revenues to strengthen fiscal independence and sustain regional development. Among these revenue sources, the Motor Vehicle Tax (PKB) and the Motor Vehicle Transfer Fee (BBNKB) play a vital role in shaping regional fiscal capacity. This study explores how both taxes contribute to the Regional Own-Source Revenue (PAD) of Central Java Province during the 2020–2024 period. Drawing on quantitative analysis and secondary data from the Central Java Regional Revenue Agency (Bapenda), the research assesses the effectiveness and contribution of PKB and BBNKB in supporting local fiscal performance. The results show that PKB consistently exerts a positive, meaningful influence on PAD, underscoring its central role in sustaining the province’s fiscal strength. In contrast, BBNKB demonstrates a weaker, less stable impact, primarily driven by changes in vehicle ownership trends and administrative challenges. When considered together, both tax instruments contribute to enhancing local fiscal capacity, although the reliance on PKB remains predominant. These findings underscore the importance of modernizing regional tax administration, particularly through digital innovation, transparent reporting systems, and community-based compliance strategies. Strengthening these mechanisms is essential to building a more resilient and autonomous fiscal framework, especially in the context of post-pandemic economic recovery and long-term regional development planning